Renewable Energy Alternatives: Bioetanol in Cassava as an Energy - Michele, Okocha (International Journal Papier Advance and Scientific Review, 2021)
The study aimed at investigating the use of cassava as potential alternative renewable energy. The study method utilized is a descriptive method of making bioethanol from cassava on a research facility scale. 50 kg of new cassava, include 1.5 ml of alpha-amylase protein at that point warm for 30-60 minutes Include 1 g of bread yeast, 65 g of urea, and 14 g of NPK. The efficiency of cassava at the cultivate level is 14.3 - 18.8 to/ha, in spite of the fact that information from the inquire about center reports that efficiency can reach 30-40 tons / ha. It is prescribed that cassava as a biofuel fabric comes from assortments that have the taking after properties: tall starch substance, tall abdicate potential, safe to biotic and abiotic stresses, adaptability in cultivating and collecting age.